The Analysis of Junior High School Students’ Metacognitive Skills to Solve the Science Problems - Nurul Hidayah Almubarokah; Tri Lestari; Isnawati Lujeng Lestari; Charles Adeputra Sufardi; Agustinus Michael (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2025)
In creating educational objectives aligned with the Learning Compass 2030, it is essential to establish a learning environment where students feel comfortable and to apply learning strategies suited to the characteristics of the learners. The objective of this research is to map students' metacognitive skills to understand their learning strategies in solving science-related problems. This study employs a mixed-methods approach, which involves collecting both quantitative and qualitative data, integrating the two forms of data, and using diverse research designs. The quantitative data were obtained from administering metacognitive skills tests and questionnaires, while qualitative data were gathered from student interviews. The research yielded several findings: (1) expert validity results for the metacognitive skills instrument indicated it is valid, (2) trial testing of the instrument showed it to be reliable and valid, (3) the profile of students' metacognitive skills across all indicators was found to be low in three different schools, and (4) there was a high response rate. The novelty of this research lies in mapping students' metacognitive skills in three different regions after the COVID-19 pandemic.